Ciclazindol and mazindol on glucose uptake into human isolated skeletal muscle: no interaction of mazindol with methysergide. - Kirby, M J (1977)
1 Ciclazindol, like mazindol, produced a significant concentration-dependent increase in glucose-uptake into human skeletal muscle in both the presence and absence of insulin. 2 Methysergide, which inhibits the action of fenfluramine on glucose-uptake into skeletal muscle, did not influence the effect of mazindol.